Fra i Sacrari delle Dolomiti: Pensieri liberi passeggiando per Pocol, Pian De Salesei, Pordoi, Quero (L'architettura delle città - The Journal of the Scientific Society Ludovico Quaroni, 2025)
The Dolomite mountain range was the scene of many battles during the First World War. Many young soldiers lost their lives fighting on both fronts. Several memorials were built in their commemoration, whose shapes present interesting design aspects related to the concept of remembrance.